Effect of intraoperative muscle relaxation reversal on the success rate of motor-evoked potential recording in patients undergoing spinal surgery: study protocol for a randomised controlled trial. Issue 5 (2nd May 2022) - Jian, Minyu; Ma, Bo; Liu, Haiyang; Wang, Chengwei; Liang, Fa; Zhou, Yang; Qiao, Hui; Han, Ruquan
Abstract : Introduction: Transcranial motor-evoked potentials (TceMEPs) is conventionally performed without neuromuscular blockade (NMB) because of its potential interference with neuromuscular junction and signal interpretation. Sugammadex is the first highly selective antagonist that binds to rocuronium and can rapidly and effectively reverse NMB. This study aims to evaluate the success rate of intraoperative muscle relax reversal by sugammadex on intraoperative TceMEP recording. Methods and analysis: We will conduct a single-centre randomised controlled study. In total, 162 patients undergoing thoracic or lumbar spinal surgery will be randomly divided into the sugammadex group or control group at a ratio of 1:1. Total intravenous anaesthesia by propofol and remifentanil will be performed in both groups. In the sugammadex group, patients will receive continuous infusion of rocuronium to produce a blockade maintained for at least two twitches in train-of-four, rocuronium infusion will be discontinued and 2 mg/kg sugammadex will be given while performing TceMEPs monitoring. In the control group, rocuronium infusion will be discontinued and the same volume of saline will be infused while performing TceMEPs monitoring. The primary aim of this study is to evaluate the success rate of TceMEPs recording between two groups. Ethics and dissemination: The approval for the study was certificated by the Ethical Committee of Beijing Tiantan Hospital, Capital Medical University on, 16 July 2021 (KY2021-082-02). The study was registered on clincaltrials.gov on 25 October 2020. Our study might guide neuromuscular blockade plans in TceMEPs monitoring undergoing spinal surgery. The findings of the study will be published in peer-reviewed journals and will be presented at national or international conference. Trial registration number: NCT04608682 .